Circulating tumour DNA and melanoma survival: A systematic literature review and meta-analysis. (January 2021) - Gandini, Sara; Zanna, Ines; De Angelis, Simone Pietro; Cocorocchio, Emilia; Queirolo, Paola; Lee, Jenny H; Carlino, Matteo S; Mazzarella, Luca; Achutti Duso, Bruno; Palli, Domenico; Raimondi, Sara; Caini, Saverio
Graphical abstract: Abstract: We reviewed and meta-analysed the available evidence (until December 2019) about circulating tumour DNA (ctDNA) levels and melanoma patients survival. We included twenty-six studies (>2000 patients overall), which included mostly stage III-IV cutaneous melanoma patients and differed widely in terms of systemic therapy received and somatic mutations that were searched. Patients with detectable ctDNA before treatment had worse progression-free survival (PFS) (summary hazard ratio (SHR) 2.47, 95 % confidence intervals (CI) 1.85–3.29) and overall survival (OS) (SHR 2.98, 95 % CI 2.26–3.92), with no difference by tumour stage. ctDNA detectability during follow-up was associated with poorer PFS (SHR 4.27, 95 %CI 2.75–6.63) and OS (SHR 3.91, 95 %CI 1.97–7.78); in the latter case, the association was stronger (p = 0.01) for stage IV vs. III melanomas. Between-estimates heterogeneity was low for all pooled estimates. ctDNA is a strong prognostic biomarker for advanced-stage melanoma patients, robust across tumour (e.g. genomic profile) and patients (e.g. systemic therapy) characteristics.